Analisis Nilai Estetika Lirik Lagu “Kepada Noor” dan Implikasinya dalam Pembelajaran Menulis Puisi - Zarani, Davina Indah; Turahmat (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the aesthetic values contained in the song lyrics Kepada Noor by Panji Sakti and their implications for poetry writing instruction at the senior high school level. This research employed a qualitative descriptive approach using documentation and content analysis techniques to examine the aesthetic elements within the lyrics. The analysis focused on identifying and classifying diction, figures of speech, and imagery that contribute to the lyrical beauty. The findings revealed 30 aesthetic data consisting of 10 diction data, including 4 denotative and 6 connotative expressions; 7 figures of speech, comprising 4 personifications, 1 metaphor, 1 hyperbole, and 1 simile; and 13 imagery data, including 6 visual images, 5 kinesthetic images, and 2 auditory images. These elements collectively create expressive, imaginative, and meaningful language constructions. The study demonstrates that the lyrics of Kepada Noor possess strong aesthetic qualities and can serve as an effective instructional medium in poetry writing learning. Furthermore, the song lyrics help students understand and apply aesthetic elements in literary works more contextually and creatively.